2021
DOI: 10.2147/ijgm.s343538
|View full text |Cite
|
Sign up to set email alerts
|

Does Red Cell Distribution Width Predict Hip Fracture Mortality Among the Arab Population? A Single-Center Retrospective Cohort Study

Abstract: Background Hip fractures impose significant morbidity and mortality. Red cell distribution width (RDW) appears to be an emerging tool in predicting mortality following hip fractures. Several factors can influence the RDW value including genetic factors and ethnicity. The purpose of the study was to assess the relation between RDW level at admission and hip fracture mortality within 6 months among Arab/Middle East populations. Methods We conducted a single-center retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…After assessing for eligibility, 18 studies were excluded because they did not have full text ( n = 2), did not have mortality data ( n = 3), did not have RDW data ( n = 4), did not include our target population ( n = 3), did not assess our outcome of interest ( n = 1), involved letters to editors ( n = 2), had missing data ( n = 1), used an irrelevant study design or approach ( n = 1), or shared a database with another study that was included in the review ( n = 1). As a result, 10 studies remained to perform the meta-analysis [ 11 , 12 , 13 , 14 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After assessing for eligibility, 18 studies were excluded because they did not have full text ( n = 2), did not have mortality data ( n = 3), did not have RDW data ( n = 4), did not include our target population ( n = 3), did not assess our outcome of interest ( n = 1), involved letters to editors ( n = 2), had missing data ( n = 1), used an irrelevant study design or approach ( n = 1), or shared a database with another study that was included in the review ( n = 1). As a result, 10 studies remained to perform the meta-analysis [ 11 , 12 , 13 , 14 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 10 studies were conducted between 2013 and 2022 in Türkiye [ 31 , 33 , 34 , 36 ], Jordan [ 32 ], China [ 12 , 35 ], the United Kingdom [ 11 ], Israel [ 13 ], and Peru [ 14 ], involving a total of 5834 patients (2241 men and 3593 women) with a pooled mean age of 87.61 ± 3.21 years. These studies comprised four retrospective cohort studies [ 13 , 32 , 33 , 36 ], two retrospective case–control studies [ 31 , 34 ], three prospective cohort studies [ 11 , 12 , 35 ], and one retrospective and prospective cohort study [ 14 ]. Eight studies indicated that all patients included in their analyses underwent surgery after sustaining hip fractures [ 11 , 13 , 14 , 32 , 33 , 34 , 35 , 36 ], one study reported that 113 of 1479 patients received conservative treatment only [ 12 ], and one study did not provide any information regarding post-fracture interventions [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was also from single center but included patients over 3.5 years duration. 10 They reported a 12.8% mortality rate within 6 months of surgery. Our study is a multicenter study from 4 major hospitals covering about 50% of hip fracture care in Jordan.…”
Section: Previous Studies About Hip Fractures In Jordanmentioning
confidence: 98%
“…There were only two single-center studies from Jordan that discussed hip fracture-related issues. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation